2018
DOI: 10.1084/jem.20171151
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mutant Asxl1 perturbs hematopoiesis and promotes susceptibility to leukemic transformation

Abstract: Nagase and Inoue et al. generated a novel Asxl1 mutant mouse model to mimic clonal hematopoiesis and myelodysplastic syndromes caused by ASXL1 mutations and elucidated the effects of mutant versus wild-type ASXL1 on hematopoiesis, gene expression, and chromatin state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 66 publications
(121 reference statements)
6
128
0
Order By: Relevance
“…ASXL1 mutations occur in various types of myeloid malignancies, most commonly are frameshift or nonsense variants, and have been associated with poor prognosis in AML, MDS, and CMML . Functional studies in mice showed that Asxl1 haploinsufficiency leads to the development of MDS‐like disease, and expression of a truncated Asxl1 protein induces altered function of HSC and increased susceptibility to leukemic transformation …”
Section: Functional Implications Of Recurrent Gene Mutations In Chmentioning
confidence: 99%
See 1 more Smart Citation
“…ASXL1 mutations occur in various types of myeloid malignancies, most commonly are frameshift or nonsense variants, and have been associated with poor prognosis in AML, MDS, and CMML . Functional studies in mice showed that Asxl1 haploinsufficiency leads to the development of MDS‐like disease, and expression of a truncated Asxl1 protein induces altered function of HSC and increased susceptibility to leukemic transformation …”
Section: Functional Implications Of Recurrent Gene Mutations In Chmentioning
confidence: 99%
“…59 Functional studies in mice showed that Asxl1 haploinsufficiency leads to the development of MDS-like disease, and expression of a truncated Asxl1 protein induces altered function of HSC and increased susceptibility to leukemic transformation. [60][61][62]…”
Section: Functional Implications Of Recurrent Gene Mutations In Chmentioning
confidence: 99%
“…We and others have shown that Asxl1 mutations can result in loss of function and lead to MDS-like disease in mice (14,15). Studies from several groups have also shown that truncated mutations of Asxl1 generated gain of function and dominant-negative function, leading to myeloid leukemia (52)(53)(54). Future work to investigate the hematopoietic phenotypes in truncated Asxl1 and haploinsufficient Nf1-mutant mice is warranted.…”
Section: Discussionmentioning
confidence: 94%
“…Using a conditional knock‐in approach, Nagase et al showed that expression of the AML‐associated ASXL1 mutant led to global reductions of H3K4me3 and H2AK119ub. H3K27me3 levels were reduced specifically at HoxA loci, despite minimal changes in global H3K27me3 (Nagase et al , ). In line with the observed reduction in H2AK119ub, Asada et al .…”
Section: Epigenetic Dysregulation In Paediatric Amlmentioning
confidence: 99%